The crisis and its impact on unemployed people in Europe: qualitative survey in seven EU Member States. Final report - Paugam, Serge; Giorgetti, Camila; Gloukoviezof, Georges; Guerra, Isabel; Laparra, Miguel; Papadopoulos, Despina; Tucci, Ingrid; Vlase, Ionela (Luxembourg, 2014)
"As part of the package on "Coping strategies with crisis", this study analyses experiences of unemployment in a recession and is based on a qualitative survey of a sample of over a hundred unemployed people from selected EU Member States.